Impact of Free Trade Agreement Use on Import Prices - Hayakawa, Kazunobu (World Bank, Washington, DC, 2018)
This paper examines the impact of free trade agreement (FTA) use on import prices. For this analysis, it employs establishment-level import data with information on tariff schemes, that is, the FTA and most-favored-nation schemes used for importing. Unlike previous studies, this paper estimates the effects of FTA use on prices by controlling for differences in importing-firm characteristics. There are three main findings. First, the effect of FTA use is overestimated when not controlling for importing firm-related fixed effects. Second, on average, firms' FTA use reduces tariffs by 12 percentage points and raises import prices by 3.6-6.7 percent. Third, in general, a price rise resulting from the costs of complying with rules of origin was not found.